Evaluating 10 years of premature mortality costs associated with liver cancer: a retrospective economic analysis of productivity loss in Spain - Josep Darbà; Meritxell Ascanio (BMJ Open)
Objectives To assess the economic burden of premature mortality due to liver cancer in Spain over 10 years (2013–2022) using a retrospective economic analysis.Design A population-based retrospective study using the Human Capital approach.Setting We analysed national registry data from the Spanish National Institute of Statistics on mortality, employment and wage structure. Sensitivity analyses were conducted using discount rates of 0%, 3% and 6%.Participants All individuals who died from liver cancer between 2013 and 2022, with a focus on the working-age population under 65 years of age.Primary and secondary outcome measures Primary outcomes included years of potential life lost (YPLL), years of potential labour productive life lost (YPLPLL) and associated productivity losses due to premature liver cancer mortality. Secondary outcomes involved trend analyses of productivity loss and YPLL over time, and assessment of sex-specific and age-specific differences in productivity losses.Results Between 2013 and 2022, 36 635 individuals died from liver cancer, including 6622 individuals of working age. This led to 9924–12 068 YPLL annually. The cumulative productivity loss was €12.88 billion (range: €12.52–€13.26 billion).Conclusions These findings highlight the substantial economic impact of liver cancer mortality in Spain and underscore the importance of targeted prevention and screening programmes for high-risk populations.